The consequences of shifting single wagon consignments to the road infrastructure and its environmental impact - Cempírek Václav; Drahotský Ivo; Novák Petr (CRC Press, 2015)
This paper contains the conclusions of a study, which was conducted for a rail cargo carrier. One of the main activities of the carrier is the transportation of single wagon consignments as well as the set of more complete wagon loads. It is the transport of the cargo loaded in one carriage or in a more wagons (maximally five wagons) with single consignment note (way-bill). This business segment is for business entity economically unprofitable because revenues do not cover the total costs incurred for this activity. If this business segment was repealed, the entire transport volume of goods would be transferred to road cargo. The main aim of this study was to analyze the single consignments (i.e. one complete wagon loads) as well as complete wagon loads transportation. The analysis is focused on the period from 2008 to 2013.
Důsledek přesunu jednotlivých vozových zásilek na silniční infrastrukturu a dopad na životní prostředí
Keywords: single wagon consignments; transport; train; cargo; jednotlivé vozové zásilky; doprava; vlak; náklad